Synthesis and Characterization of Manganese Dithiocarbamate Complexes: New Evidence of Dioxygen Activation - Petra Martini; Alessandra Boschi; Lorenza Marvelli; Licia Uccelli; Stefano Carli; Giuseppe Cruciani; Erika Marzola; Anna Fantinati; Juan Esposito; Adriano Duatti (Molecules, 2021)
(1) Background: Metal dithiocarbamate compounds have long been the subject of research due to their ease of formation, excellent properties and potential applications. However, manganese complexes with dithiocarbamates, to our knowledge, have never been used for medical imaging applications. With the aim of developing a new class of mononuclear manganese(II)-based agents for molecular imaging applications, we performed a specific investigation into the synthesis of mononuclear bis-substituted Mn(II) complexes with dithiocarbamate ligands. (2) Methods: Synthesis in either open or inert atmosphere at different Mn(II) to diethyldithiocarbamate molar ratios were performed and the products characterized by IR, EA, ESI-MS and XRD analysis. (3) Results: We found that only under oxygen-free atmospheric conditions the Mn(II) complex MnL2, where L = diethyldithiocarbamate ligand, is obtained, which was further observed to react with dioxygen in the solid state to form the intermediate superoxo Mn(III) complex [MnL2(η2-O2)]. The existence of the superoxo complex was revealed by mass spectroscopy, and this species was interpreted as an intermediate step in the reaction that led the bis-substituted Mn(II) complex, MnL2, to transform into the tris-substituted Mn(III) complex, MnL3. A similar result was found with the ligand L’ (= bis(N-ethoxyethyl)dithiocarbamate). (4) Conclusions: We found that in open atmosphere and in aqueous solution, only manganese(III) diethyldithiocarbamate complexes can be prepared. We report here a new example of a small-molecule Mn(II) complex that efficiently activates dioxygen in the solid state through the formation of an intermediate superoxide adduct.